The influence of service quality, customer satisfaction and bank image on customer loyalty in Palestinian Islamic banks - Alnaser, Feras Mohammad
Customer loyalty in Islamic banking has been a major concern to practitioners due to increasing local and global competition from conventional and Islamic banks. The Islamic banking sector in Palestine has been seen at the lowest level in terms ofnumber, clients and assets compared to conventional banks. Aside of stagnant growth, banking sector in Palestine has been criticised by customers with respect to service quality. In early studie , SERVQUAL service quality model was extensively used to investigate service quality issues in the banking sector. However, previous service quality model did not include the dimension of culture to measure service quality. Past studies also supported that service quality, satisfaction and image were among key factors to customer loyalty in banking industry. Therefore, this study was conducted to investigate the influence of Pakistan Service Quality dimensions (PAKSERV), subjective norms, customer satisfaction and bank image on customer loyalty of Palestine Islamic banking customers. Two main theories used in this study, Theory of Reasoned Action (TRA) and Expectancy Disconfirmation Theory (EDT). The respondents for this study were Islamic banks customers in Palestine. A total of 500 questionnaires were distributed in three cities: Nablus , Ramallah and Hebron using convenience sampling method. Therefore, 357J) completed questionnaires were retrieved, giving a response rate of 71 % of the original sample. The data was collected in six weeks beginning of September 2017. The research model was empirically tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. Results of SEM depicted that tangibility, reliability, assurance, sincerity, personalization, formality and subjective norms explained 80% variance in customer satisfaction. Additionally, customer satisfacnren was found positively impact on customer loyalty. Customer satisfaction was found to mediate the relationship between service quality dimensions (tangibility, reliability, assurance, sincerity, personalization, formality and Subjective norms) and customer loyalty. Moreover, the study also confirmed that bank image moderates the relationship between customer satisfaction and customer loyalty. The results of this study have provided several implications for practitioners and researchers. The findings of this study provided insights to top managements of banking industry with regard to the importance of the mediating role of customer satisfaction and subjective norms as the most influencing construct.